2020
DOI: 10.1111/jorc.12357
|View full text |Cite
|
Sign up to set email alerts
|

Self‐management program for adolescents with chronic kidney disease: A randomized controlled trial

Abstract: Background It is important to develop self‐management behaviours in adolescents to prevent chronic kidney disease progression. Objectives This study evaluates the effect of a self‐management program that was developed based on individual and family self‐management theory to aid adolescents with chronic kidney disease in the acquisition of competencies in the management of their disease. Design This is a randomized controlled study. Participants The study was conducted with 20 intervention and 20 control patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…Individuals who can manage their self‐efficacy and care can reduce the incidence of complications associated with hemodialysis by exhibiting better adherence to their dietary regimen, regular medication, and fluid restriction 10,11 . One study that examined the effect of self‐efficacy on blood pressure, salt restriction, and compliance with hemodialysis in patients found that the patients reduced their salt intake, had a low interdialytic weight gain, took anti‐hypertensives more regularly, and had better compliance with hemodialysis after a 12‐week follow‐up 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals who can manage their self‐efficacy and care can reduce the incidence of complications associated with hemodialysis by exhibiting better adherence to their dietary regimen, regular medication, and fluid restriction 10,11 . One study that examined the effect of self‐efficacy on blood pressure, salt restriction, and compliance with hemodialysis in patients found that the patients reduced their salt intake, had a low interdialytic weight gain, took anti‐hypertensives more regularly, and had better compliance with hemodialysis after a 12‐week follow‐up 12 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 One study that examined the effect of self-efficacy on blood pressure, salt restriction, and compliance with hemodialysis in patients found that the patients reduced their salt intake, had a low interdialytic weight gain, took anti-hypertensives more regularly, and had better compliance with hemodialysis after a 12-week follow-up. 12 Individuals with self-efficacy will be able to accomplish their daily activities without being dependent on others. The Chronic Disease Self-Management Program (CDSMP) was applied to patients undergoing hemodialysis twice a week, and its effectiveness was investigated.…”
mentioning
confidence: 99%